2017
DOI: 10.1371/journal.pone.0170699
|View full text |Cite
|
Sign up to set email alerts
|

α-Iso-Cubebene Inhibits PDGF-Induced Vascular Smooth Muscle Cell Proliferation by Suppressing Osteopontin Expression

Abstract: α-Iso-cubebene (ICB) is a dibenzocyclooctadiene lignin contained in Schisandra chinensis (SC), a well-known medicinal herb that ameliorates cardiovascular symptoms. Thus, we examined the effect of ICB on vascular smooth muscle cell (VSMC) proliferation, a key feature of diverse vascular diseases. When VSMCs primary cultured from rat thoracic aorta were stimulated with PDGF (1–10 ng/ml), cell proliferation and osteopontin (OPN) expression were concomitantly up-regulated, but these effects were attenuated when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…One should also consider the other important mechanisms and cytokine interactions involved in the pulmonary fibrosis induction and progression, such as combined action of PDGF and TGF- β 1. [61] PDGF itself, which was found to be upregulated in SWCNT-treated animals, [26] also participates in upregulating the expression of OPN [86,87] and may implement its action in part through the OPN promotion, which has been shown for the smooth muscle cells. [88,89] There’s little data as of yet regarding the possible OPN upstream effects on PDGF signaling, but interestingly, one of the recent papers describes the hampering of Focal adhesion kinase (FAK) phosphorylation by PDGF in osteoblasts and fibroblasts upon the recombinant OPN treatment, [90] thus potentially reducing their migration activity.…”
Section: Discussionmentioning
confidence: 99%
“…One should also consider the other important mechanisms and cytokine interactions involved in the pulmonary fibrosis induction and progression, such as combined action of PDGF and TGF- β 1. [61] PDGF itself, which was found to be upregulated in SWCNT-treated animals, [26] also participates in upregulating the expression of OPN [86,87] and may implement its action in part through the OPN promotion, which has been shown for the smooth muscle cells. [88,89] There’s little data as of yet regarding the possible OPN upstream effects on PDGF signaling, but interestingly, one of the recent papers describes the hampering of Focal adhesion kinase (FAK) phosphorylation by PDGF in osteoblasts and fibroblasts upon the recombinant OPN treatment, [90] thus potentially reducing their migration activity.…”
Section: Discussionmentioning
confidence: 99%
“…α-Cubebene identified in 'Halhalı' olive leaf as the major VC is a dibenzocyclooctadiene lignin and it has a potential antioxidant property [12]. It has previously been identified in Schisandra chinensis herb as the most plentiful VC [13]. This plant is a well-known medicinal herb that ameliorates cardiovascular symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Also, ICB has neuroprotective [ 25 27 28 ] and anti-inflammatory effects, the latter of which was attributed to the inhibition of endothelial expression of adhesion molecules [ 26 ]. In our previous study, ICB has been suggested to be therapeutically useful in proliferative vascular diseases by inhibiting VSMC proliferation [ 29 ]. Although ICB has been suggested to have beneficial effects on various cardiovascular symptoms, the mechanisms underlying its potential protective effects have not yet been fully investigated.…”
Section: Discussionmentioning
confidence: 99%